2015
DOI: 10.1002/2014jd022420
|View full text |Cite
|
Sign up to set email alerts
|

Near‐cloud aerosols in monsoon environment and its impact on radiative forcing

Abstract: In order to understand the near-cloud aerosol properties and their impact on radiative forcing, we utilized in situ aircraft measurements of aerosol particles and cloud droplets during the Cloud Aerosol Interaction and Precipitation Enhancement Experiment carried out over the Indian subcontinent in the monsoon season. From the measurement of aerosol size distribution of diameter range from 0.1 to 50 μm, we reported that aerosol concentrations could be enhanced by 81% and the effective diameter (d eff , μm) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
(132 reference statements)
0
7
0
Order By: Relevance
“…The appearance of higher σ in the highly diluted cloud edge region of monsoon cloud could be caused by collision‐coalescence of the larger droplets (Devenish et al , ) which are not present in pre‐monsoon clouds (Prabha et al , ). As the environment is moist and aerosols near clouds are pre‐moistened as illustrated by (Konwar et al , ), there is partial evaporation of droplets, which broaden the spectra in downdrafts and may activate in cloud updrafts. The presence of collision‐coalescence in monsoon deep convective cloud is reported by Prabha et al () and Khain et al ().…”
Section: Resultsmentioning
confidence: 99%
“…The appearance of higher σ in the highly diluted cloud edge region of monsoon cloud could be caused by collision‐coalescence of the larger droplets (Devenish et al , ) which are not present in pre‐monsoon clouds (Prabha et al , ). As the environment is moist and aerosols near clouds are pre‐moistened as illustrated by (Konwar et al , ), there is partial evaporation of droplets, which broaden the spectra in downdrafts and may activate in cloud updrafts. The presence of collision‐coalescence in monsoon deep convective cloud is reported by Prabha et al () and Khain et al ().…”
Section: Resultsmentioning
confidence: 99%
“…A cloud flag was formulated and activated to in‐cloud 20 s before and 20 s after each of the aircraft trajectory data points that show either liquid water content above 0.02 g/m 3 or a total FSSP particle concentration above 25 cm −3 . In addition to cloud filtering, this also excluded the near‐cloud areas, where high relative humidity values might contribute to aerosol hygroscopic growth and, thus, bias the measurements (Konwar et al, ). Regardless, we found that in most cases, the major contribution to column‐integrated PSD was made by the cloud‐free planetary boundary layer (PBL) segments of the flight, where relative humidity remained well below 80%.…”
Section: Model and Datamentioning
confidence: 99%
“…Since the advent of observational techniques for monitoring these variations from surface, air and space, the diversity of sensors with improved precision and accuracy has increased and corresponding innovative methods have been developed [8][9][10][11]. Aircraft measurements are becoming increasingly important for model validation studies because they can document aerosol variations in remote regions where access to ground-based observations is difficult or unavailable, and offer observations with higher temporal resolution than can typically be attained with satellites [12][13][14].…”
Section: Introductionmentioning
confidence: 99%